A Theological Framework Approach with Gentle Mentoring to Effectiveness Re-Evangelizing Pentecostal-Charismatic Congregations - Bangun, Mardona; Tampubolon, Topan M. T.; Barutu, Juwita R (Journal of World Science, 2023)
The Pentecostal charismatic movement is growing very fast around the world in quantity. Christian doctrine has little meaning, so spiritual and social behavior becomes distorted according to personal feelings and lifestyles, becoming selfish or individualist. This study aims to show that re-evangelizing charismatic Pentecostals using a gentle attitude is very important so that the big picture of Christian theology can be conveyed and well accepted by them so that the understanding of doctrine and attitude of worship becomes correct. It used a descriptive quantitative approach with a sample of 258 respondents by conducting multiple linear regressions . The study used a quantitative approach with a sample of 258 respondents. The R square value derived from the Influence of Bible understanding and knowledge of the person of Jesus Christ on church behaviour was 52%; other influences were absent in this study. The F table value is 141,377 with a significance value of 0.000 or < 0.5%, indicating that there is a simultaneous influence between the variables of Bible understanding and knowledge of the person of Jesus Christ on the congregation's behaviour is significant. The t value obtained was 8,195 for the Bible understanding of church behaviour variable with a significance of 0.000 or <0.5%, meaning there is a significant partial influence. The t-table value for the variable understanding of the person of Jesus Christ is 12,057 with a significance of 0.000 or <0.5%, meaning there is a significant partial influence. Gentle personal re-evangelism presents the big picture of God's redemptive narrative.